Die tschechisch-ungarischen Beziehungen im 19. Jahrhundert und der Ausgleich : Historisches Institut der Akademie der Wissenschaften der Tschechischen Republik - Hlavačka, Milan (Pázmány Law Review, 2023)
During the period from the Enlightenment to the 1848/1849 revolution, Czech-Hungarian contacts and eff orts to get to know each other better had three main levels. The first level we can call the enlightened aristocratic interest in the knowledge and welfare of the country. It was based on individual relationships. The contacts of the founder of the Hungarian National Museum and the National Library, Count Ferenc Széchényi, who maintained various relationships with the Czech crown lands, belong. This interaction resulted in particular from his family and friendly relationships with the Bohemian nobility.